2008
DOI: 10.1016/j.math.2006.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The initial effects of a Mulligan's mobilization with movement technique on range of movement and pressure pain threshold in pain-limited shoulders

Abstract: There is little known about the specific manual therapy techniques used to treat painfully limited shoulders and their effects on range of movement (ROM) and pressure pain threshold (PPT). The objective of this study was to investigate the initial effects of a Mulligan's mobilization with movement (MWM) technique on shoulder ROM in the plane of the scapula and PPT in participants with anterior shoulder pain. A repeated measures, double-blind randomized-controlled trial with a crossover design was conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 87 publications
4
91
0
3
Order By: Relevance
“…Teys et al (2008) measured the shoulder ROM after applying Mulligan's mobilization with movement (MWM) technique once to patients with painful shoulder conditions and found that it increased by 15.3% 7) . Souza et al (2008) reported that they applied Maitland joint mobilization grades III and IV on 25 persons and their ankle dorsiflexion ROM increased immediately after joint mobilization 8) , which showed the immediate positive effect of manual therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Teys et al (2008) measured the shoulder ROM after applying Mulligan's mobilization with movement (MWM) technique once to patients with painful shoulder conditions and found that it increased by 15.3% 7) . Souza et al (2008) reported that they applied Maitland joint mobilization grades III and IV on 25 persons and their ankle dorsiflexion ROM increased immediately after joint mobilization 8) , which showed the immediate positive effect of manual therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the effect of physiotherapy on clinical outcomes in patients with shoulder disorders are unclear, with systematic reviews reporting divergent findings (Dorrestijn et al , 2009, Ho et al , 2009, Michener et al , 2004, van den Dolder et al , 2012. It is challenging to determine effects of physical modalities (e.g., exercise, manual therapy, electrotherapy) on clinical outcomes in multimodal randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…Mobilization With Movement (MWM) has been shown to reduce pain levels, increase range of motion (Abbott, 2001, Mulligan, 2006, Vicenzino, Hing, 2011, and function in patients with shoulder pain (Mulligan, 2006, Teys et al , 2008, Vicenzino, Hing, 2011. Correction of bony positional fault, neurophysiological effects or a combination of both have been proposed as the underlying mechanisms of MWM (Vicenzino et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although an improvement in shoulder functionality was found, the results are not similar to other studies about Mulligan technique which state that shoulder functionality is correlated to glenohumeral AROM. 31 Teys et al 16 showed the effectiveness of the Mulligan technique on pain in adults younger than 60 years. Although the study had a small sample size (n = 24), statistically significant results were found concerning immediate effects after 1 MWM treatment session.…”
Section: Discussionmentioning
confidence: 99%
“…The patient must repeat the movement several times to get an improvement that lasts over time. 14,15 The initial effects of MWM in adults were assessed by Teys et al 16 who proved its effectiveness in increasing shoulder AROM and decreasing positional faults. Therefore, it may be an effective technique in the physical therapy treatment for shoulder dysfunction, as this addresses passive and active shoulder structures.…”
Section: Introductionmentioning
confidence: 99%